On defining a model driven architecture for an enterprise e-health system. Issue 8 (21st October 2018) - Atanasovski, Blagoj; Bogdanovic, Milos; Velinov, Goran; Stoimenov, Leonid; Dimovski, Aleksandar S.; Koteska, Bojana; Jankovic, Dragan; Skrceska, Irena; Kon-Popovska, Margita; Jakimovski, Boro
ABSTRACT: The national e-health systems implemented in Serbia as "MojDoktor" (MyDoctor) and in Macedonia as "MojTermin" (MyAppointment) are based on the same integrated health information platform. Its architecture was designed to allow for process oriented development with agile methodologies. This methodology allowed for fast deployment and adoption, but a change in the architecture to a more formal approach is required to assure its extensibility, soundness, interoperability and standardization. In this paper, we propose a formalization of the system design and its implementation as a Model Driven Architecture®. We develop a set of formal models on several abstraction levels and explain how different layers of the MDA framework are covered using them. We also propose a model for data transformations that will provide interfaces for interoperability between an external and our system.